(untitled) (Texas Journal of Medical Science, 2024)
This article examines ways to improve the effectiveness of tympanoplasty in children. An analysis of existing surgical methods and an evaluation of factors influencing the success of operations in pediatric patients have been conducted. The primary focus is on selecting optimal materials for tympanic membrane reconstruction and minimizing postoperative complications. The study also offers recommendations for postoperative care aimed at enhancing surgical outcomes and hearing restoration. The research is based on a retrospective analysis of clinical data from patients who underwent tympanoplasty, with the goal of identifying key factors affecting surgical outcomes.